ORAL HYGIENE STATUS IN CRETINISM PATIENTS - varshini, Vindhiya; Vikraman, Rakshagan; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
INTRODUCTIONCretinism is a condition of severely stunted physical and mental growth owing to untreated congenital deficiency of thyroid hormone (congenital hypothyroidism), usually owing to maternal hypothyroidism. Dental characteristics of hypothyroidism are thick lips, a large-sized tongue, etc. Delayed eruption of primary and permanent dentitions can be observed. This study deals with the oral hygiene status in cretinism patients. MATERIALS AND METHODS A questionnaire was prepared and distributed among the undergraduate and postgraduate doctors in Saveetha Dental Hospital and nearby clinics. A total of 70 participants attended this survey. The questionnaire was based on the awareness and treatment of oral hygiene in cretinism patients. RESULTS: 60% of the respondents were aware of cretinism. 56% were aware of stunted physical and mental growth. 52% come across any cretinism patients during practice. 87% were aware that treating cretinism patients is different from treating normal patients. 46% were aware that cretinism patients have compromised periodontal health - bone resorption. 68% feel orthodontic treatment is necessary for treating cretinism patients. (Table 1) CONCLUSIONCretinism patients usually vary from normal children in their external appearance, and most of them face difficulty in phonetics and mastication. Hence, special care must be taken while treating them. Malocclusion is misalignment or incorrect relation between the teeth of two dental arches. In cretinism patients, although the teeth reach normal size, they are frequently crowded due to the small size of the jaws. Hence, malocclusion and oral hygiene should be diagnosed and treated in cretinism patients. Correction of malocclusion may reduce the risk of tooth decay and help relieve excessive pressure on the temporomandibular joint.